Low-cost 590MPa-grade hot-dip galvanized dual-phase steel and preparation method thereof

By adopting low-cost chemical composition and process flow, 590MPa grade hot-dip galvanized double-phase steel was prepared, which solved the problems of high cost and poor forming performance in the prior art, and achieved low-cost and high-performance steel preparation.

CN119392090APending Publication Date: 2025-02-07PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411603977.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The process of preparing 590MPa grade hot-dip galvanized duplex steel in the prior art contains precious metal elements, which leads to an increase in cost, and a small amount of bainite is contained in the microstructure, resulting in a low elongation after break, which is not conducive to obtaining good forming performance.

Method used

Use low-cost chemical components for smelting, including C: 0.06%~0.10%, Si: 0.30%~0.55%, Mn: 1.70%~2.00%, etc., through processes such as smelting, hot rolling, acid rolling and hot-dip galvanizing. Prepare 590MPa grade hot-dip galvanized double-phase steel.

Benefits of technology

The preparation of 590MPa grade hot-dip galvanized duplex steel with low cost and high safety performance has been achieved. The microstructure is composed of 68%-73% ferrite and 27%-32% martensite, and the yield strength is 345MPa~390MPa , the tensile strength is 590MPa~630MPa, the elongation A80 value is 27.0%~33.0%, the yield strength ratio is 0.54-0.66, and the porosity reaming rate is 40%-55%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392090A_ABST
    Figure CN119392090A_ABST
Patent Text Reader

Abstract

The invention discloses low-cost 590MPa-grade hot-dip galvanized dual-phase steel and a preparation method thereof. The dual-phase steel comprises the following chemical components: C, Si, Mn, P, S, Als, Cr, N and the balance of Fe and inevitable impurities. The microstructure of the low-cost 590 MPa-grade hot-dip galvanized dual-phase steel prepared through the method is composed of 68%-73% of ferrite and 27%-32% of martensite distributed in an island shape. According to the low-cost 590 MPa-grade hot-dip galvanized dual-phase steel, the yield strength ranges from 345 MPa to 390 MPa, the tensile strength ranges from 590 MPa to 630 MPa, the elongation A80 value ranges from 27.0% to 33.0%, the yield ratio ranges from 0.54 to 0.66, and the hole expansion rate ranges from 40% to 55%. The average grain size of the ferrite is 3.8 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cold-rolled strip production, and in particular relates to a 590MPa-grade hot-dip galvanized duplex steel plate suitable for production by a hot-dip galvanizing unit. Background Art

[0002] High strength of automobile steel is the most effective way to solve safety, low carbon emissions and low energy consumption at the same time. Dual-phase steel has good strength, plasticity and processing properties, and has become the most widely used advanced high-strength steel for automobiles, and 590MPa grade is the most widely used product. Through reasonable composition and process design, low-cost and high-performance 590MPa grade hot-dip galvanized dual-phase steel will greatly promote the lightweighting of automobiles. At the same time, with the increasing calls for recycling of steel materials, the implementation of the "material elementalization" concept has reduced costs and facilitated recycling, and green considerations have been taken into account throughout the product life cycle (manufacturing-use-recycling) from the design stage.

[0003] The prior art process for preparing the hot-dip galvanized dual-phase steel contains relatively more precious metal elements (such as Mo and Nb), which increases the alloy cost. The microstructure contains a small amount of bainite, which results in a relatively low elongation after fracture, which is not conducive to obtaining good forming properties. In addition, the rapid cooling rate in the prior art process is relatively fast and is difficult to be extended to conventional production lines.

[0004] Therefore, how to prepare hot-dip galvanized dual-phase steel with low cost and high safety performance has become a difficult problem that urgently needs to be solved. Summary of the invention

[0005] Based on this, in view of the above-mentioned deficiencies in the prior art, a method for producing 590 MPa grade hot-dip galvanized duplex steel sheet using a hot-dip galvanizing unit is provided.

[0006] In order to achieve the above purpose, the following technical solutions are adopted: The present invention provides a method for preparing a low-cost 590MPa grade hot-dip galvanized dual-phase steel, comprising the following steps: (a) Smelting process: smelting according to the chemical composition of low-cost 590MPa grade hot-dip galvanized dual-phase steel and casting into slabs, wherein the chemical composition of the low-cost 590MPa grade hot-dip galvanized dual-phase steel includes, by mass percentage, C: 0.06%-0.10%, Si: 0.30%-0.55%, Mn: 1.70%-2.00%, P≤0.018%, S≤0.007%, Als: 0.015%-0.070%, Cr: 0.15%-0.40%, N≤0.0055%, and the remaining elements are Fe and unavoidable impurities; (b) hot rolling process: the slab obtained in step (a) is subjected to heating, descaling, rough rolling, finish rolling and laminar cooling to obtain a hot rolled coil; (c) Pickling process: pickling the hot-rolled coil obtained in step (b) and then cold-rolling it into a cold-rolled steel strip; (d) Hot-dip galvanizing process: The cold-rolled steel strip obtained in step (c) is heated, soaked, slowly cooled, quickly cooled, and evenly kept warm before entering a zinc bath for galvanizing. After exiting the zinc bath, the steel strip is air-cooled to room temperature to obtain a low-cost 590 MPa grade hot-dip galvanized duplex steel.

[0007] In some embodiments, the chemical composition of the low-cost 590MPa grade hot-dip galvanized dual-phase steel includes, by mass percentage: C: 0.075%~0.10%, Si: 0.40%~0.50%, Mn: 1.80%~1.95%, Al: 0.025%~0.060%, P≤0.015%, S≤0.005%, Cr: 0.15%~0.25%, N≤0.0040%, and the remainder is Fe and unavoidable impurities.

[0008] In some embodiments, one or more of the following are included: In step (b), the final rolling temperature is 860°C-910°C, the laminar cooling adopts the front-stage cooling method, the upper and lower header cooling rates are 60%-80% and 80%-100%, and the coiling temperature is 500°C-560°C; In step (c), the cold rolling reduction ratio is 62%-78%; In step (d), the cold-rolled steel strip is first heated to 300°C, 700°C and 800°C-832°C at heating rates of 8°C / s-13°C / s, 1.5°C / s-6.6°C / s and 0.8°C / s-3.5°C / s respectively; after being heat-insulated for 30s-65s, the cold-rolled steel strip is slowly cooled to 680°C-712°C at a rate of 1.8°C / s-8.5°C / s, and rapidly cooled to 440°C-460°C at a rate of 35°C / s-58°C / s.

[0009] In some embodiments, in step (c), as the thickness of the cold-rolled steel strip increases, the cold-rolling reduction ratio gradually decreases, and the cold-rolling reduction ratio decreases by 3-5% for every 0.5 mm increase in the thickness of the cold-rolled steel strip.

[0010] In some embodiments, in step (d), the time for entering the zinc bath for galvanizing treatment is 5s to 30s.

[0011] In some embodiments, in step (d), the unit speed is 85 m / min-125 m / min; as the cold-rolled thickness of the material increases, the unit speed gradually decreases, and the unit speed decreases by 10 m / min for every 0.5 mm increase in the thickness of the cold-rolled strip.

[0012] In some embodiments, the flattening elongation is 0.30% to 0.60%, and the flattening elongation decreases by 0.05% for every 0.5 mm increase in material thickness.

[0013] The present invention also provides a low-cost 590MPa grade hot-dip galvanized dual-phase steel, which is prepared by the method as described above.

[0014] In some embodiments, the microstructure of the low-cost 590 MPa grade hot-dip galvanized dual-phase steel consists of 68%-73% ferrite and 27%-32% martensite distributed in islands. In some embodiments, the yield strength of the low-cost 590MPa grade hot-dip galvanized dual-phase steel is 345MPa-390MPa, the tensile strength is 590MPa-630MPa, and the elongation A is 80 The value is 27.0%~33.0%, the yield strength ratio is 0.54-0.66, and the hole expansion rate is 40%-55%.

[0015] The present invention has the following beneficial technical effects: The microstructure of the low-cost 590MPa grade hot-dip galvanized dual-phase steel disclosed in the present invention is composed of 68%-73% ferrite and 27%-32% island-shaped martensite. The yield strength of the low-cost 590MPa grade hot-dip galvanized dual-phase steel is 345MPa-390MPa, the tensile strength is 590MPa-630MPa, and the elongation A 80 The value is 27.0%~33.0%, the yield strength ratio is 0.54-0.66, the hole expansion rate is 40%-55%. The average grain size of ferrite is 3.8μm. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 This is a scanning electron microscope image of a low-cost 590MPa grade hot-dip galvanized dual-phase steel according to an embodiment of the present invention; Figure 2 : is a stress-strain curve diagram of a low-cost 590MPa grade hot-dip galvanized dual-phase steel according to an embodiment of the present invention. DETAILED DESCRIPTION

[0018] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.

[0019] It should be understood that the embodiments of the present invention shown in the exemplary embodiments are only illustrative. Although only a few embodiments are described in detail in the present invention, it is easy for those skilled in the art to appreciate that multiple modifications are feasible without actually departing from the teaching of the subject matter of the present invention. Accordingly, all such modifications should be included within the scope of the present invention. Without departing from the gist of the present invention, other replacements, modifications, changes and deletions may be made to the design, operating conditions and parameters of the following exemplary embodiments.

[0020] Based on the above purpose, a first aspect of an embodiment of the present invention provides a low-cost 590MPa grade hot-dip galvanized dual-phase steel, whose chemical composition, by mass percentage, includes: C: 0.06%~0.10%, Si: 0.30%~0.55%, Mn: 1.70%~2.00%, P≤0.018%, S≤0.007%, Als: 0.015%~0.070%, Cr: 0.15%-0.40%, N≤0.0055%, and the remaining elements are Fe and unavoidable impurities.

[0021] In a preferred embodiment, the chemical composition of the low-cost 590MPa grade hot-dip galvanized dual-phase steel includes, by mass percentage, C: 0.075%-0.10%, Si: 0.40%-0.50%, Mn: 1.80%-1.95%, Al: 0.025%-0.060%, P≤0.015%, S≤0.005%, Cr: 0.15%~0.25%, N≤0.0040%, and the balance is Fe and unavoidable impurities.

[0022] Among them, the microstructure of low-cost 590MPa grade hot-dip galvanized dual-phase steel is composed of 68%-73% ferrite and 27%-32% island-shaped martensite. The yield strength of low-cost 590MPa grade hot-dip galvanized dual-phase steel is 345MPa~390MPa, the tensile strength is 590MPa~630MPa, and the elongation is A 80 The value is 27.0%~33.0%, the yield strength ratio is 0.54-0.66, the hole expansion rate is 40%-55%. The average grain size of ferrite is 3.8μm.

[0023] Carbon (C): C is the element with the most obvious solid solution strengthening effect in steel materials. It is also an element that expands the austenite zone. It directly affects the content of ferrite, martensite and residual austenite in hot-dip galvanized duplex steel after critical zone treatment. When the C content is too low, the stability of austenite and the hardenability of martensite decrease. It is necessary to increase the content of alloying elements such as Mn, Cr, and Mo to ensure strength, which leads to increased costs. Excessive C content leads to decreased forming and welding effects. Therefore, the C content of the present invention is 0.060% to 0.100%, preferably 0.075 to 0.100%.

[0024] Silicon (Si): Si can be dissolved in ferrite and austenite to improve the strength of steel. Its effect is second only to C and P, and stronger than Mn, Cr, Ti and Ni. Si can also inhibit the precipitation of carbides, allowing the dissolved C atoms to fully enrich in austenite, thereby improving the strength of martensite. However, when the Si content is too high, the surface iron oxide scale formed by Si in the heating furnace is difficult to remove, which increases the difficulty of descaling and seriously affects the surface quality of hot-dip galvanized steel sheets. Therefore, the Si content of the present invention is 0.30~0.55%, preferably 0.40~0.50%.

[0025] Manganese (Mn): Adding Mn improves hardenability and reduces critical cooling rate within the cooling rate capacity of conventional continuous annealing / galvanizing lines. Manganese also has a solid solution strengthening effect, which will help strengthen the ferrite phase. Manganese reduces the temperature range of austenite to ferrite transformation. In addition, Mn is a good deoxidizer and desulfurizer. Mn can combine with C to form a variety of carbides to play a role in precipitation strengthening, and can also be dissolved in the matrix to enhance the solid solution strengthening effect. Mn is easy to combine with S to form a high melting point compound MnS, thereby eliminating or weakening the hot brittleness caused by FeS and improving the hot working properties of steel. Mn can improve the stability of austenite and shift the C curve to the right, thereby significantly reducing the critical cooling rate of martensite. However, when the Mn content is too high, it will lead to increased costs and segregation, so that the transverse and longitudinal anisotropy of the strip increases. Therefore, in the present invention, the Mn content is 1.70% to 2.00%, preferably 1.80 to 1.95%.

[0026] Aluminum (Al): Al is a common deoxidizer in steel. It can also form AlN to pin the grain boundaries, thereby refining the grains. In addition, Al has a similar effect to Si and can inhibit the precipitation of carbides, thereby making the austenite fully carbon-rich. When the Al content is low, it is difficult to completely remove the O element in the molten steel. When the Al content is too high, a large amount of Al2O3 inclusions are easily generated, affecting the cleanliness of the steel. Therefore, the Als content in the present invention is 0.015% to 0.070%, preferably 0.025% to 0.060%.

[0027] Chromium (Cr): Cr is a medium-strong carbide-forming element. Like manganese, it can improve the hardenability of steel. When added to steel in combination with other alloying elements, it can greatly improve the hardenability of steel, thereby delaying the pearlite transformation and bainite transformation, and expanding the coiling window. Cr is also a solid solution strengthening element, which strengthens the matrix. On the other hand, since Cr has similar effects to Mo but has obvious cost advantages, a certain amount of Cr is added to hot-dip galvanized duplex steel. At the same time, Cr will also cause a decrease in plasticity and deteriorate the forming and welding properties of steel. Therefore, the Cr content in the present invention is 0.15%~0.40%, preferably 0.15%~0.25%.

[0028] Phosphorus (P): P is a harmful element in steel, which seriously reduces the plasticity and deformation properties of steel. The lower its content, the better. Considering the cost, the content of P in the present invention is controlled to P≤0.018%, preferably ≤0.015%.

[0029] Sulfur (S): S is a harmful element in steel, which seriously affects the formability of steel. The lower its content, the better. Considering the cost, the content of S in the present invention is controlled to S≤0.007%, preferably ≤0.005%.

[0030] Nitrogen (N): N is an impurity element in steel. Due to its small atomic size, it can easily enter the gaps between iron elements, significantly increase lattice distortion and greatly increase strength, but it will significantly deteriorate the plasticity and toughness of steel. At the same time, N can easily combine with Al, B, and Ti in steel to form second phases such as AlN, BN, and TiN, which strengthen and deteriorate the plasticity and toughness of steel. Especially when the N content is too high, it combines with Ti to form liquid TiN, which can reach micron level in size. Not only does it not play a strengthening role, but it also causes stress concentration and forms crack sources. The content of N element needs to be strictly controlled. Therefore, the N content in the present invention is ≤0.0055%, preferably 0.0040%.

[0031] A second aspect of the embodiments of the present invention provides a method for preparing a low-cost 590 MPa grade hot-dip galvanized dual-phase steel, comprising the following steps: (a) Smelting process: smelting according to the chemical composition of low-cost 590MPa grade hot-dip galvanized dual-phase steel and casting into slabs, wherein the chemical composition of the low-cost 590MPa grade hot-dip galvanized dual-phase steel includes, by mass percentage, C: 0.06%-0.10%, Si: 0.30%-0.55%, Mn: 1.70%-2.00%, P≤0.018%, S≤0.007%, Als: 0.015%-0.070%, Cr: 0.15%-0.40%, N≤0.0055%, and the remaining elements are Fe and unavoidable impurities; (b) hot rolling process: the slab obtained in step (a) is subjected to heating, descaling, rough rolling, finish rolling and laminar cooling to obtain a hot rolled coil; (c) Pickling process: the hot-rolled coil obtained in step (b) is pickled and then cold-rolled into a cold-rolled steel strip of 0.5 mm to 2.5 mm, i.e., a thin steel strip; (d) Hot-dip galvanizing process: The cold-rolled steel strip obtained in step (c) is heated, soaked, slowly cooled, quickly cooled, and evenly kept warm before entering a zinc bath for galvanizing. After exiting the zinc bath, the steel strip is air-cooled to room temperature to obtain a low-cost 590 MPa grade hot-dip galvanized duplex steel.

[0032] In some embodiments, the chemical composition of the low-cost 590MPa grade hot-dip galvanized dual-phase steel includes, by mass percentage: C: 0.075%-0.10%, Si: 0.40%-0.50%, Mn: 1.80%-1.95%, Al: 0.025%-0.060%, P≤0.015%, S≤0.005%, Cr: 0.15%~0.25%, N≤0.0040%, and the remainder is Fe and unavoidable impurities.

[0033] In some embodiments, one or more of the following are included: In step (b), the final rolling temperature is 860°C-910°C, the laminar cooling adopts the front-stage cooling method, the upper and lower header cooling rates are 60%-80% and 80%-100%, and the coiling temperature is 500°C-560°C; In step (c), the cold rolling reduction ratio is 62%-78%; In step (d), the cold-rolled steel strip is first heated to 300°C, 700°C and 800°C-832°C at heating rates of 8°C / s-13°C / s, 1.5°C / s-6.6°C / s and 0.8°C / s-3.5°C / s respectively; after being heat-insulated for 30s-65s, the cold-rolled steel strip is slowly cooled to 680°C-712°C at a rate of 1.8°C / s-8.5°C / s, and rapidly cooled to 440°C-460°C at a rate of 35°C / s-58°C / s.

[0034] In some embodiments, in step (c), as the thickness of the cold-rolled steel strip increases, the cold-rolling reduction ratio gradually decreases, and the cold-rolling reduction ratio decreases by 3-5% for every 0.5 mm increase in the thickness of the cold-rolled steel strip.

[0035] In some embodiments, in step (d), the time for entering the zinc bath for galvanizing treatment is 5s to 30s.

[0036] In some embodiments, in step (d), the unit speed is 85 m / min-125 m / min; as the cold-rolled thickness of the material increases, the unit speed gradually decreases, and the unit speed decreases by 10 m / min for every 0.5 mm increase in the thickness of the cold-rolled strip.

[0037] In some embodiments, the flattening elongation is 0.30% to 0.60%, and the flattening elongation decreases by 0.05% for every 0.5 mm increase in material thickness.

[0038] Example This embodiment provides low-cost 590MPa grade hot-dip galvanized dual-phase steel sheets of embodiments 1-4, and comparative examples 1-2 with other compositions and processes, whose chemical compositions are shown in Table 1; Table 1 Chemical composition of low-cost 590MPa grade hot-dip galvanized duplex steel (wt.%) serial number C Si Mn P S Cr N Als Example 1 0.078 0.42 1.82 0.008 0.003 0.18 0.0032 0.033 Example 2 0.080 0.4 1.85 0.007 0.005 0.20 0.0028 0.040 Example 3 0.095 0.48 1.92 0.008 0.004 0.24 0.0029 0.037 Example 4 0.084 0.45 1.88 0.009 0.003 0.22 0.0023 0.042 Comparative Example 1 0.120 0.10 2.10 0.020 0.015 0.48 0.0038 0.008 Comparative Example 2 0.040 0.85 1.35 0.023 0.014 0.10 0.0045 0.100 The specific process of the preparation method of the above-mentioned low-cost 590MPa grade hot-dip galvanized dual-phase steel sheet is as follows: A. Smelting process: After the smelting process, a dual-phase steel slab with the chemical composition shown in Table 1 is prepared; B. Hot rolling process: The slab is heated, descaled, hot rolled and laminar cooled to obtain a hot rolled coil. The specific hot rolling process parameters are shown in Table 2. Table 2 Main process parameters of hot rolling of low-cost 590MPa grade hot-dip galvanized dual-phase steel serial number Final rolling temperature / ℃ Coiling temperature / ℃ Cooling rate of upper and lower headers ℃ / s Example 1 885 535 75%、100% Example 2 875 540 75%、100% Example 3 870 545 75%、100% Example 4 903 548 75%、100% Comparative Example 1 850 550 75%、100% Comparative Example 2 918 615 75%、100% C. Pickling process: After the hot-rolled coil is pickled, it is cold-rolled into thin strip steel. The hot-rolled plate thickness, cold-rolled plate thickness and cold-rolling reduction ratio are shown in Table 3.

[0039] Table 3 Low-cost 590MPa grade hot-dip galvanized dual-phase steel cold-rolled raw materials, finished products and reduction ratio serial number Hot rolled plate thickness / mm Cold rolled sheet thickness / mm Cold rolling reduction rate / % Example 1 3.85 1.00 74 Example 2 5.90 2.00 66 Example 3 5.00 1.50 70 Example 4 6.60 2.50 62 Comparative Example 1 5.00 1.50 70 Comparative Example 2 5.00 1.50 70 D. Hot-dip galvanizing process: The cold-rolled thin strip is first heated to 300℃, 700℃ and 800~832℃ at heating rates of 8℃ / s ~13℃ / s, 1.5℃ / s ~6.6℃ / s and 0.8℃ / s ~3.5℃ / s respectively; after being evenly heated for 30~65s, it is slowly cooled to 680℃~712℃ at a rate of 1.8℃ / s~8.5℃ / s and then rapidly cooled to 440~460℃ at a rate of 35℃ / s ~58℃ / s; after being evenly heated for a period of time, it enters the zinc pool for galvanizing treatment, the time is 5s~30s, and it is air-cooled to room temperature after exiting the zinc pool. The unit speed is 85 m / min-125m / min. As the cold-rolled thickness of the material increases, the unit speed gradually slows down. For every 0.5mm increase in the thickness of the cold-rolled thin strip, the unit speed decreases by 10m / min. The flattening elongation range is 0.30%~0.60%, and the flattening elongation decreases by 0.05% for every 0.5mm increase in material thickness. The specific hot-dip galvanizing process parameters are shown in Table 4: Table 4 Main process parameters of low-cost 590MPa grade hot-dip galvanized duplex steel

[0040] The microstructure of the 590MPa grade hot-dip galvanized dual-phase steel prepared by the above process is as follows: Figure 1 The stress-strain curve is shown in Figure 2 The performance of the hot-dip galvanized 590MPa grade duplex steel was tested in accordance with GB / T228-2010 "Methods for tensile test of metallic materials at room temperature", and the hole expansion performance of the hot-dip galvanized duplex steel was tested in accordance with GB / T 24524-2009 "Methods for hole expansion test of metallic materials thin plates and thin strips", as shown in Table 5: Table 5 Mechanical properties of low-cost 590MPa grade hot-dip galvanized duplex steel

[0041] In summary, the low-cost 590MPa grade hot-dip galvanized duplex steel disclosed in the embodiment of the present invention optimizes the carbon content, so that strong plasticity can be guaranteed without using the more expensive Mo element; the silicon element can be dissolved in ferrite and austenite to increase the strength of the steel, and the silicon content is optimized so that it will not be too high or too low. Each process is regulated according to the product thickness specifications, and the product structure and performance stability are improved by controlling the parameters. The yield strength is 345MPa~390MPa, the tensile strength is 590MPa~630MPa, and the elongation A 80 The value is 27.0%~33.0%, the yield strength ratio is 0.54-0.66, and the hole expansion rate is 40%-55%. The average grain size of ferrite is 3.8μm and the component cost is low. The performance can meet the existing production needs, which will greatly promote the lightweight of automobiles and has a strong market application prospect.

[0042] 590MPa grade hot-dip galvanized duplex steel requires higher plasticity (elongation A 80 Value ≥ 21%) and yield strength ratio so that downstream users can obtain good stamping forming effects, and good hole expansion rate to meet the requirements of flanging and hole expansion. Plasticity index elongation A of implementation case 1-4 80 The values ​​are all greater than or equal to 27.5%, the yield strength ratio is low (≤0.619%), the hole expansion rate is high (≥42%), and the strength-plasticity ratio is good. Comparative Example 1 adds C, Mn, and Cr elements to achieve the strength of 780MPa (802MPa) and other product requirements, but the plasticity is low (elongation A 80 The value is only 16%), and the hole expansion rate is low (only 28%), which is not conducive to stamping and hole expansion and flanging. At the same time, the high C content will also deteriorate the welding performance (the carbon equivalent Ceq is high). The strength of comparative example 2 does not meet the requirements of 590MPa grade products (the yield strength is 285MPa, which is lower than the standard 340MPa, and the tensile strength is 526MPa, which is lower than the standard requirement of 590MPa).

[0043] The above are exemplary embodiments disclosed in the present invention, but it should be noted that various changes and modifications may be made without departing from the scope of the embodiments disclosed in the claims. Although the elements disclosed in the embodiments of the present invention may be described or required in individual form, they may also be understood as multiple unless explicitly limited to the singular.

[0044] A person skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the disclosure of the embodiments of the present invention (including the claims) is limited to these examples; under the concept of the embodiments of the present invention, the technical features in the above embodiments or different embodiments can also be combined, and there are many other changes in different aspects of the above embodiments of the present invention, which are not provided in detail for the sake of simplicity. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the embodiments of the present invention should be included in the protection scope of the embodiments of the present invention.

Claims

1. A method for preparing low-cost 590MPa grade hot-dip galvanized dual-phase steel, characterized in that: The following steps are involved: (a) Smelting process: Smelting according to the chemical composition of low-cost 590MPa grade hot-dip galvanized duplex steel and casting into slabs, wherein the chemical composition of the low-cost 590MPa grade hot-dip galvanized duplex steel includes, by mass percentage: C: 0.06%~0.10%, Si: 0.30%~0.55%, Mn: 1.70%~2.00%, P≤0.018%, S≤0.007%, Als: 0.015%~0.070%, Cr: 0.15%~0.40%, N≤0.0055%, the remaining elements are Fe and unavoidable impurities; (b) hot rolling process: the slab obtained in step (a) is subjected to heating, descaling, rough rolling, finish rolling and laminar cooling to obtain a hot rolled coil; (c) Pickling process: pickling the hot-rolled coil obtained in step (b) and then cold-rolling it into a cold-rolled steel strip; (d) Hot-dip galvanizing process: The cold-rolled steel strip obtained in step (c) is heated, soaked, slowly cooled, quickly cooled, and evenly kept warm before entering a zinc bath for galvanizing. After exiting the zinc bath, the steel strip is air-cooled to room temperature to obtain a low-cost 590 MPa grade hot-dip galvanized duplex steel.

2. The method for preparing low-cost 590MPa grade hot-dip galvanized dual-phase steel according to claim 1, characterized in that: The chemical composition of the low-cost 590MPa grade hot-dip galvanized dual-phase steel includes, by mass percentage, C: 0.075%-0.10%, Si: 0.40%-0.50%, Mn: 1.80%-1.95%, Al: 0.025%-0.060%, P≤0.015%, S≤0.005%, Cr: 0.15%-0.25%, N≤0.0040%, and the balance is Fe and unavoidable impurities.

3. The method for preparing low-cost 590MPa grade hot-dip galvanized dual-phase steel according to claim 1, characterized in that: Include one or more of the following: In step (b), the final rolling temperature is 860°C-910°C, the laminar cooling adopts the front-stage cooling method, the upper and lower header cooling rates are 60%-80% and 80%-100%, and the coiling temperature is 500°C-560°C; In step (c), the cold rolling reduction ratio is 62%-78%; In step (d), the cold-rolled steel strip is first heated to 300°C, 700°C and 800°C-832°C at heating rates of 8°C / s-13°C / s, 1.5°C / s-6.6°C / s and 0.8°C / s-3.5°C / s respectively; after being heat-insulated for 30s-65s, the cold-rolled steel strip is slowly cooled to 680°C-712°C at a rate of 1.8°C / s-8.5°C / s, and rapidly cooled to 440°C-460°C at a rate of 35°C / s-58°C / s.

4. The method for preparing low-cost 590MPa grade hot-dip galvanized dual-phase steel according to claim 1 or 3, characterized in that: In step (c), as the thickness of the cold-rolled steel strip increases, the cold-rolling reduction rate gradually decreases. For every 0.5 mm increase in the thickness of the cold-rolled steel strip, the cold-rolling reduction rate decreases by 3-5%.

5. The method for preparing low-cost 590MPa grade hot-dip galvanized dual-phase steel according to claim 1 or 3, characterized in that: In step (d), the time for entering the zinc bath for galvanizing treatment is 5s to 30s.

6. The method for preparing low-cost 590MPa grade hot-dip galvanized dual-phase steel according to claim 1 or 3, characterized in that: In step (d), the unit speed is 85 m / min-125 m / min; as the cold-rolled thickness of the material increases, the unit speed gradually decreases, and the unit speed decreases by 10 m / min for every 0.5 mm increase in the thickness of the cold-rolled strip.

7. The method for preparing low-cost 590MPa grade hot-dip galvanized dual-phase steel according to claim 1 or 3, characterized in that: The flattening elongation is 0.30%~0.60%. For every 0.5mm increase in material thickness, the flattening elongation decreases by 0.05%.

8. A low-cost 590MPa grade hot-dip galvanized duplex steel, characterized in that: It is prepared by the method described in any one of claims 1 to 7.

9. The low-cost 590MPa grade hot-dip galvanized dual-phase steel according to claim 8, characterized in that: The microstructure of the low-cost 590MPa grade hot-dip galvanized dual-phase steel consists of 68%-73% ferrite and 27%-32% martensite distributed in islands.

10. The low-cost 590MPa grade hot-dip galvanized dual-phase steel according to claim 8, characterized in that: The yield strength of the low-cost 590MPa grade hot-dip galvanized dual-phase steel is 345MPa~390MPa, the tensile strength is 590MPa~630MPa, and the elongation A 80 The value is 27.0%~33.0%, the yield strength ratio is 0.54-0.66, and the hole expansion rate is 40%-55%.

Citation Information

Cited By

  • Production method of 590Mpa galvanized dual-phase steel with low cost and high surface quality

    CN121826510A

  • 590MPa-grade hot-dip galvanized dual-phase steel and production method thereof

    CN121951394A

  • 590mpa grade hot dip galvanized dual phase steel and method of producing the same

    CN121951394B

  • Low-carbon hot-rolled substrate hot-galvanized dual-phase steel and production method thereof

    CN122214751A